Adapting functional assessments for use in a new context: A balancing act. (September 2013) - Schulze, Christina; Page, Julie; Kottorp, Anders; Lilja, Margareta
Abstract: Objective: It is common practice today to process translations and adaptations of assessments through a committee review in order to render them suitable for use in a new context. The aim of this study was to elaborate issues that arise during the harmonization process in a committee review illustrated by the example of adapting the Pediatric Evaluation Disability Inventory (PEDI) for a German-speaking region of Europe to gain semantic, conceptual, and cultural equivalence of the translated version. Methods: The harmonization process was based on the subtle balancing act of (i) staying close to the original assessment, while adapting the translation to the new context, (ii) making decisions and reaching a consensus, (iii) the group dynamics versus planned course of the review committee. Results: The findings illustrate that achieving equivalence between the original and the target translated assessment was not always unproblematic and the risk of remaining misfitting items was found. The findings also highlight further influencing elements and discuss the challenges researchers face when planning to take on the task of translating and adapting an assessment. Conclusions: Some recommendations for conducting a committee review are formulated.